THE SILENT ENEMY FROM THE FIST - VIKING DISEASE - Stoiljković, Vera (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Dupuytren’s contracture (DK) is a progressive idiopathic fibrosis of the superficial palmar fascia caused by changes in the palmar aponeurosis, resulting in flexion contracture of the fingers with inability to extend the fingers. The disease, also called Viking’s disease, is present in 8% of the world’s population, more common in men, and heredity, which shows variable expression, plays an important role in its etiology. The pathogenesis of DK is still unclear, and involves the formation of collagen nodules that progress into fibrous bands at the places of greatest pressure between the dermis and fascia. The diagnosis is established only by clinical examination, and the treatment can be conservative and surgical. Conservative treatment is reserved for patients with milder symptoms and no finger contracture, while surgical treatment is the gold standard in the therapy of people in whom the resulting contracture limits the function of the hand and/or flexion of the proximal interphalangeal joint by ≥15º and/or the metacarpophalangeal joint by ≥30º. The aim of this paper is to present the current findings related to DK.